KAPASITAS PEMERINTAH DESA DALAM PENGELOLAAN KEUANGAN DESA DI DESA MAJU TAHUN 2019 (Studi Pada Desa Aji Kuning Kecamatan Sebatik Tengah Kabupaten Nunukan): Array - Iman Surya; Sry Reski Mulka; Hafizh Yudhistira Inderawaspada (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
This research is motivated by the large distortion of development inequality between villages and cities, in addition to the strengthening of the village's position as the spearhead of national development based on Law Number 6 of 2014 concerning Villages. In implementing village governance, there are many crucial problems, such as the lack of use of village funds which is oriented towards accelerating the capacity of human resources (HR), neglect of these conditions has an effect of underdevelopment. In addition, the lack of community empowerment efforts by the village government, this condition is exacerbated by the weak skills of village apparatus human resources in the implementation of financial management even though they have complete facilities. This study uses the basis of the capacity analysis proposed by Kapucu (2012) which consists of aspects of organizational aspirations, strategy, organizational skills, human resources, infrastructure, organizational structure, and culture. The results showed that the capacity of Aji Kuning Village based on the aspirations aspect went well because there was a clear vision and mission that could be implemented in development programs based on community participation, then the strategic capacity was more oriented towards strengthening infrastructure and implementing village government compared to community empowerment efforts. This is in line with the weakness of networking as a result of weak human resources in the position of village financial affairs, this condition has an impact on the excessive workload delegated to village officials even though they have their own duties and functions. In addition, the organizational cultural capacity of Aji Kuning Village emphasizes the principle of equality and transparency in various village financial governance plans (APBDes)